Viral Infections as the most Frequent Causes of Undifferentiated Fever in Children Living in the Lower Mekong Region: A Systematic Review - Xuan Duong Tran; Thi Loi Dao; Nhu Ngoc Nguyen; Van Thuan Hoang; Philippe Gautret (Dr. Sulaiman Al Habib Medical Journal)
To summarize common infections responsible for undifferentiated fever in children living in the lower Mekong region. This review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Eighteen articles were included, including eight studies that were performed on both children and adults. A total of 1,017,923 patients were included in these studies, and viral infections were the most common causes of infections. Dengue virus was detected in 6%–72.8% of the patients, chikungunya virus in 15.8%–66.0% of the patients, and influenza A virus in 3.8%–18.8% of the patients. Rickettsia sp. was detected in 0%–18.9% of the patients, Leptospira was detected in 0%–27.2% of the patients, and Salmonella typhi in 2.6%–37.5% of the patients. Viral fever is the most common cause of undifferentiated fever among children in the lower Mekong region. Testing for microbial pathogens may help reduce inappropriate antibiotic use.